Use of cone-beam computed tomography in patients under 25 years of age from Talca, Chile - Bastián Arancibia Palomo; Juan Schilling Lara; Alejandro Schilling Quezada; Gloria Correa-Beltrán; Alejandro Hidalgo Rivas (Editorial Ciencias Médicas, 2017)
Introduction: dental cone-beam computed tomography is a technology of recent introduction in Chile and there is no information regarding its use in young populations. From the point of view of radiation protection, its use with young patients is particularly worrisome, due to their greater susceptibility to ionizing radiation. Objective: determine the indications and exposure parameters of cone-beam computed tomography in patients under 25 years of age cared for in a 12-month period at a private maxillofacial radiology center in Talca, Chile. Methods: a observational descriptive cross-sectional study was conducted. Data were collected from 240 examinations. The exposure parameters used by a SkyView set (MyRay, Imola, Italy) were recorded, and note was taken of the clinical indications for each test. Data were processed by descriptive statistics using Fisher's test. Results: the main indication was tooth location (46 %), followed by planning of third molar extraction (25 %), implant planning (7.1 %) and temporomandibular joint (6 %). The small field of view was the most commonly used in all age groups (81 %). The milliampere-time product was 100.7 mAs for preschool children and 110.1-110.9 mAs for adolescents and young adults. The effective dose was 52.4 µSv for preschool children and 62.1 µSv for adolescents and young adults. Partial rotation was used in 100 % of the tests. 96 % of the indications complied with Guideline No 172 of the European Commission. Conclusions: the main indications were tooth location, planning of third molar extraction, implant planning and temporomandibular joint, in that order. The small field of view was the most commonly used. Total rotation was found in all cases. Milliampere-time product and effective dose did not show any significant differences between the age groups studied.